Can Isotopes Be Used as Lead Tracers in Shooting-Range Soils? - Andrés Rodríguez-Seijo; Knut Endre Sjåstad; Vladislav Chrastný (Applied Sciences, 2022)
Lead isotopes have been widely used to assess the sources of Pb in the soil environment since lead isotopes ratios have a specific signature that allows us to use them as environmental tracers. However, some lead sources are difficult to be identified. This article contains the lead isotope data from soils and shot pellets collected in an abandoned shooting range (NW Spain). Twelve soil and three-shot pellet samples were randomly collected and analyzed using MC-ICP-MS. The isotope ratios are shown, and analyses proved that Pb originated predominantly from the used shot pellets. Contaminated soils exhibited an isotopic composition (206Pb/207Pb, 208Pb/204Pb, 206Pb/204Pb and 208Pb/206Pb) close to some shot pellets from different manufacturers. These results offer new, valuable data for other researchers working on lead contamination research and the identification sources of Pb for adjacent areas to shooting-range facilities and for wildlife ecotoxicology. Still, the use of several ammunitions derived from different sources, such as recycled Pb, showed that it is hard to identify the lead source and these kinds of facilities.